Electrochemical immunosensor assay (EIA) for sensitive detection of E. coli O157:H7 with signal amplification on a SG–PEDOT–AuNPs electrode interface. Issue 2 (20th November 2014) - Guo, Yuna; Wang, Yu; Liu, Su; Yu, Jinghua; Wang, Hongzhi; Cui, Min; Huang, Jiadong
Abstract : The SG–PEDOT–AuNPs composites not only enhance interface electron transfer efficiency, but also offer a multivalent recognition interface for conjugating E. coli . Abstract : A novel electrochemical immunosensor assay (EIA) for highly sensitive and specific detection of Escherichia coli O157:H7 has been developed. This immunosensor is constructed by the assembly of capture antibody on SG–PEDOT–AuNPs composites modified glass carbon electrode. In the presence of target E. coli O157:H7, horseradish peroxidase (HRP)-labeled antibody is captured on the electrode surface to form a sandwich-type system via the specific identification. As a result, E. coli O157:H7 detection is realized by outputting a redox current from electro-reduction of hydrogen peroxide reaction catalyzed by HRP. In our assay, the combination of the unique properties of sulfonated graphene (SG) and gold nanoparticles (AuNPs) can not only accelerate electron transfer on electrode interface, but also provide an excellent scaffold for the conjugation of capture antibody that significantly improves the target capture efficiency and enhances the sensitivity of the biosensor. The results reveal the calibration plot obtained for E. coli O157:H7 is approximately linear from 7.8 × 10–7.8 × 10 6 colony-forming unit (cfu) mL −1 with the limit of detection of 3.4 × 10 cfu mL −1 . In addition, the biosensor has been successfully applied to the quantitative assay of E. coli O157:H7 in synthetic samples (spring water and milk). Hence, the developed electrochemical-based immunosensor might provide a useful and practical tool for E. coli O157:H7 determination and related food safety analysis and clinical diagnosis.